2010
DOI: 10.1099/vir.0.019604-0
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-associated MAPK/ERK2 phosphorylates EMD and regulates infectivity

Abstract: Infection of a cell by lentiviruses, such as human immunodeficiency virus type 1 or feline immunodeficiency virus, results in the formation of a reverse transcription complex, the preintegration complex (PIC), where viral DNA is synthesized. In non-dividing cells, efficient nuclear translocation of the PIC requires the presence of the inner nuclear lamina protein emerin (EMD). Here, we demonstrate that EMD phosphorylation is induced early after infection in primary nondividing cells. Furthermore, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Particularly, MAPK binds with the virion and induces Gag-MA phosphorylation (Cartier et al 1997;Bukong et al 2010). Inhibition of these 2 proteins in macrophages causes a reduction in EMD phosphorylation and viral integration, affecting the viral infection (Bukong et al 2010). Therefore, these proteins are likely directly or indirectly related to each other and required for HIV-1 PIC import, at least in a cell-specific manner.…”
Section: Ledgfmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, MAPK binds with the virion and induces Gag-MA phosphorylation (Cartier et al 1997;Bukong et al 2010). Inhibition of these 2 proteins in macrophages causes a reduction in EMD phosphorylation and viral integration, affecting the viral infection (Bukong et al 2010). Therefore, these proteins are likely directly or indirectly related to each other and required for HIV-1 PIC import, at least in a cell-specific manner.…”
Section: Ledgfmentioning
confidence: 99%
“…Moreover, upon viral infection, EMD is phosphorylated, which is dependent on both mitogen-activated protein kinase (MAPK) and MEK1 kinase (Bukong et al 2010). Particularly, MAPK binds with the virion and induces Gag-MA phosphorylation (Cartier et al 1997;Bukong et al 2010). Inhibition of these 2 proteins in macrophages causes a reduction in EMD phosphorylation and viral integration, affecting the viral infection (Bukong et al 2010).…”
Section: Ledgfmentioning
confidence: 99%
See 1 more Smart Citation
“…Known modifiers include the serine/threonine kinases protein kinase A (PKA; [184]), GSK3β [200], PKCδ [201], and ERK2/MAPK [202]. Emerin is also phosphorylated on multiple tyrosines by Src (Y59, Y74, Y95) [188], Abl (Y167) [188] and Her2 [188,203].…”
Section: Post-translational Modification and Regulation Of Emerinmentioning
confidence: 99%
“…2,34,47,49 It was also shown that phosphorylation of viral proteins by the virion-associated kinases plays an important role in the regulation of early steps in viral replication. 2,8,9,33,49,62,66 Recent reports from our laboratory and others demonstrated that host cell serine-threonine kinases such as mitogen-activated protein kinase (MAPK)/extracellular signalregulated kinase 2 (ERK-2) and the catalytic subunit of cyclic AMP-dependent protein kinase A (C-PKA) are incorporated within HIV-1/SIV particles. 12,27,30,33,49 Interestingly, the structural protein Gag MA (HIV-1/SIV), capsid (CA), p6, Vpr (HIV-1), and Vpx (SIV) have been reported as the substrates for the virion-associated MAPK/ERK-2.…”
mentioning
confidence: 99%